Nos tuis supplicationibus inclinati. Pope Innocent IV and the Decline of Delegated Jurisdiction in Hungary in the Mid-13th Century (Povijesni prilozi (Historical Contributions), 2024)
The paper discusses a special aspect of the Papal-Hungarian relations, namely the operation of the delegated jurisdiction after the Mongol invasion of 1241–42. The focus of the study is on the revival of the system in the 1240s, and on certain measures of Pope Innocent IV in 1252 and 1254. The first measure of this kind is traditionally considered to be a papal allowance, which was granted to King Béla IV in order to avoid his ecclesiastical and lay subjects being cited outside of the realm. This prohibition, according to the opinion of the Hungarian legal-historian, György Bónis, was annulled as early as 1259. In the present study we argue that, although the charters of Innocent IV and Alexander IV are indeed of great importance, but its impact should not to be overrated. The number of the known cases, which were supervised by papal judges significantly dropped in the 1250s. However, the reason behind this decrease cannot be explained solely with the above-mentioned papal charter, but other factors should also be considered, while we investigate this question.